Relaxed specificity of matrix metalloproteinases (MMPS) and TIMP insensitivity of tumor necrosis factor-alpha (TNF-alpha) production suggest the major TNF-alpha converting enzyme is not an MMP. - Black, R; Durie, F; Otten-Evans, C; Miller, R; Slack, J; Lynch, D; Castner, B; Mohler, K; Gerhart, M; Johnson, R; Itoh, Y; Okada, Y; et al. (1996)
Tumor necrosis factor-alpha is released from cells by a proteolytic cleavage. Previous work suggested that a specific, non-matrix metalloproteinase carries out this cleavage, but matrix metalloproteinases have also been implicated. In this paper, we report that none of the matrix metalloproteinases tested cleaved peptide substrates as specifically as the non-matrix metalloproteinase. A matrix metalloproteinase did process tumor necrosis factor-alpha extracted from COS cells, but neither tissue inhibitor of metalloproteinases-1 nor -2 blocked tumor necrosis factor-alpha processing by human monocytes. Moreover, tissue inhibitor of metalloproteinases-1 had at most a partial effect on the in vivo release of the cytokine in mice. We conclude that a non-matrix metalloproteinase is the major physiological tumor necrosis factor-alpha convertase.